IMPLEMENTATION OF PATENT AND TRANSFER OF PATENT RIGHTS ACCORDING TO INDONESIAN PATENT LAW - Kamil, Abir Rafa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
AbstractIndonesia as a member of the World Trade Organization (“WTO”) is obliged to comply with the provisions stipulated in the Trade-Related Intellectual Property Rights Agreement (“TRIPs Agreement”) especially regarding Patents; therefore, the Government of Indonesia regulates the provisions regarding Patents by Law Number 13 of 2016 concerning Patent which has been amended through Law Number 11 of 2020 Concerning Job Creation (“Indonesia Patent Law”). Article 20 of Indonesian Patent Law regulates that “the implementation of Patents must be implemented in Indonesia which can be done by making, importing, and licensing.”. Related to the protection of patent rights granted, the state also hopes to transfer technology from Patent Holders; thus, their inventions can be produced and used without paying royalties to Patent Holders. However, the provisions regulated by the Government of Indonesia stipulate that the implementation of Patent can be carried out by importing, which will result in no transfer of technology from the Patent Holders to the state; thus, it will be detrimental to Indonesia. Therefore this paper will examine and explain the impact of applying Article 20 of the Indonesian Patent Law, especially regarding the implementation of Patent and transfer of Patent Rights.AbstrakIndonesia sebagai anggota World Trade Organization (“WTO”) wajib memenuhi ketentuan yang ditetapkan dalam Trade-Related Intellectual Property Rigths Agreement (“TRIPs Agreement”) terutama mengenai Paten, oleh karena itu, Pemerintah Indonesia mengatur ketentuan mengenai Patent melalui Undang-Undang Nomor 13 Tahun 2016 tentang Paten yang telah diubah melalui Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja (“UU Paten Indonesia”). Pasal 20 UU Paten Indonesia mengatur bahwa “implementasi Paten harus dilaksanakan di Indonesia yang dapat dilakukan dengan membuat, mengimpor, dan lisensi.”. Pada dasarnya terkait dengan perlindungan Hak Paten yang diberikan, negara juga berharap untuk terjadinya peralihan teknologi dari Pemegang Paten sehingga invensi mereka dapat diproduksi dan digunakan tanpa harus membayar royalty kepada Pemegang Paten. Namun, ketentuan yang diatur oleh Pemerintah Indonesia menetapkan bahwa implementasi Paten dapat dilakukan dengan importasi yang mana hal tersebut tidak akan menghasilkan peralihan teknologi dari Pemegang Paten kepada negara sehingga akan merugikan Indonesia. Oleh karena itu paper ini akan mengkaji dan menjelaskan dampak penerapan Pasal 20 UU Paten Indonesia khususnya mengenai implementasi Paten dan transfer Hak Patent.